Analisis Penerapan Proses Akuntansi untuk Pengambilan Keputusan Strategis pada UMKM (Studi Kasus UMKM di Sawojajar Kota Malang) - Hayati, Dewi Nur; Askandar, Noor Shodiq; Afifudin, Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to analyze the application of accounting processes and strategic decision making for micro, small and medium enterprises (MSMEs). The research used is qualitative descriptive research with primary data sources and secondary data. Data collection methods through interviews and documentation. The subjects in this research are micro, small and medium enterprises (MSMEs) located in the Sawojajar, Malang City. The results of this research show that business actors, micro, small and medium (MSMEs) have not implemented the accounting process in accordance with the basic principles and concepts of accounting, because there are still MSME actors who have not applied the basic principles and concepts of accounting in recording their accounting processes, resulting in Strategic decision making cannot be done in accordance with accurate facts and data. This occurs due to the opinion of business actors that the accounting recording process is complicated and difficult to understand.Keywords: Application of accounting processes, strategic decision making, micro, small and medium enterprises (MSMEs)